THE FACTORS OF KNOWLEDGE AND FAMILY’S SUPPORT WITH THE BEHAVIOR OF GENITAL HYGIENE - Hany Nabila; Dwi Izzati Budiono; Muhammad Ilham Aldika A (UNIVERSITAS AIRLANGGA, 2020)
AbstractBackground : Adolescence is a period of transition from childhood to adulthood. When girls experience menstruation, their reproductive organs are functioning properly, so it’s important to maintain the cleanliness of the genital organs to avoid reproductive health problems such as vaginal discharge. The case number of reproductive tract infection in East Java on 2006 was 86.5%. There are many factors that influence adolescents to behave in genital hygiene, including the level of knowledge and family support. The purpose of this study was to determine there was a relationship between the level of knowledge and family support with genital hygiene behavior in adolescent. Methods: This study uses a relationship research method with a cross sectional. Thisresearch place at SMPN 1 Jabon, Sidoarjo. The sample in this study amounted to 170 people using proportional random sampling. Collecting data using a questionnaire. Data analysis used chi-square correlation test and Spearman rank correlation test. Results: From the results of this study, it was found that most of the respondents had poor knowledge (53%), adequate family support (52%), and fairly clean genital hygiene behavior (59%). There is a relationship between the level of knowledge with genital hygiene behavior in adolescent (p = 0.045), there is a relationship between family support and genital hygiene behavior in adolescent (p = 0.001). The results of multivariate analysis showed a relationship between the level of knowledge and family support with genital hygiene behavior in adolescent (p = 0.008), where family support had a significant relationship (p = 0.002).